Predicting material fatigue from material properties - Loh, Teck Yang. (2013)
The primary purpose of this report is to study how the surface properties of an aluminium alloy changes, at the initial stage of test fatigue test. The surface properties of the aluminium sample include Young’s Modulus and surface roughness. Moreover